Conflict, Tourism and Technology: Developing Comprehensive Policy for Sustainable Tourism in Kashmir Valley - Wani, Gowhar Ahmad; Peer, Arshid Hussain; Naikoo, Mohd Waseem (Revista de turism - studii și cercetări în turism, 2021)
This paper studies the fallouts of insurgency and its impact upon the growth of tourism in Kashmir Valley. As a part of study, role of technology to promote sustainable tourism growth and negatives of internet blockades are extensively explored. The simple trend analysis shows that the Tourist Influx increases in years of normalcy and falls drastically in years of disturbance. The use of technology and innovation will bring significant employment and economic benefits not only to tourism industry but also to other allied sectors of industry. However, the shutdown of internet frequently is paralyzing the day-to-day life. As a result of which an environment of fear and uncertainty is created. The study suggests that policy makers need to take broad overview of situation and a rule-based policy needed to be followed with regard to internet shutdowns. The article recommends that the institutions and stakeholders should try for comprehensive steps to ensure peace, security, and stability.